Tsietsi. - Akinola, O.C (University of Limpopo, 2017)
The setting of this play is somewhere in rural South Africa. Far left sits a shebeen. On far right is Madithunya’s home, a shack. Play opens with a choreographed dance in different parts of a very busy street. All sorts of people, traders, students, travelers are busy doing their things. Old Tsietsi, an old fellow in his late 50s, concludes his dealings with a sellerclient. He observes a heavily pregnant woman standing with someone who appears like her father, apparently, waiting anxiously to catch a taxi to the hospital. The woman appears to be experiencing labour pains. We here sounds of thunder, we see lightning and the signs of coming rain. The labouring woman exclaims…..The dancing continues and then…..
Drama staged by Lucas Mkuti at University of Limpopo NCH between 4th to 13th May, 2017.
Keywords: 808.8200968; African drama; African drama-History and criticism